How to teach listening : with audio CD - JJ, Wilson (harlow Pearson Education limited, 2008)
The How To...Series is edited by Jeremy Harmer. It is written by teachers and teacher trainers - people who know the reality of the classroom and the support teachers need to get the most out of their students - these practical, easy-to-use handbooks are a must for English teaching professionals. They'll help build your confidence and your classroom abilities and, we hope, inspire you to try out new ideas. People remember great teachers. These books help you to be one.
Keywords: An explanation of the main principles behind listening in the classroom; Practical ideas for conducting an effective listening lesson; Strategies to ensure the long term development of students$1 (Blistening skills s; A task file of photocopiable training activities